Residual Cough and Asthma-like Symptoms Post-COVID-19 in Children - Abdullah Al-Shamrani; Khalid Al-Shamrani; Maram Al-Otaibi; Ayed Alenazi; Hareth Aldosaimani; Zeyad Aldhalaan; Haleimah Alalkami; Abdullah A. Yousef; Sumayyah Kobeisy; Saleh Alharbi (MDPI AG, 2023)
Background: Coronavirus disease 2019 (COVID-19) has rapidly spread worldwide and is characterized by different presentations ranging from asymptomatic to severe pneumonia. COVID-19 affects all age groups, including pediatric patients. We observed numerous children complaining of a cough post-COVID-19, even if it was trivial. The most reported persistent symptoms after recovery from COVID-19 were insomnia, coughing, fatigue, dyspnea, loss of taste and/or smell, and headache. To date, residual cough post-COVID-19 has been reported in pediatrics and adolescents. Method: we conducted a retrospective study, with a self-administered questionnaire by the patient or caregiver, 12 months post-COVID-19-infection. Result: A total of 94.8% of patients were Saudi citizens and were mainly from the southern region of Saudi Arabia (50.0%). Mothers (64.4%) submitted most of the results. The ages were as follows: 6-14 years (51.0%), 3-5 years (32.3%), and younger than 2 years of age (only 16.7%). Females accounted for 41.7% of those studied. Nearly half of the patients (48.5%) had had a previous COVID-19 infection in 2022, with only 2.1% infected in 2019. Only 27/194 (13.9%) patients required hospital admission, and 7 of them (4.2%) required intensive care treatment. A total of 179 (92.2%) patients still reported persistent symptoms 4 weeks post-COVID-19-infection. A cough was reported in 69.8% of patients, followed by cough and wheezing in 12.3%. The cough was described as dry in 78.0% and nocturnal in 54.1%, while 42.5% did not notice any diurnal variation. For those reporting residual cough, 39.3% found that it affected school attendance and daily activities, 31.1% reported associated chest pain, 51.9% associated it with wheezing, and 27.1% associated it with shortness of breath. For 54.4%, the residual cough lasted less than one month, while 31.4% reported a 1-2 month duration. Only 1.0% had a duration of cough of more than 3 months. For cough relief, 28.2% used bronchodilators, 19.9% used cough syrup, 16.6% used a combination of bronchodilators and steroid inhalers, and 1.7% used antibiotics. Surprisingly, 33% attempted herbal remedies for cough relief. Sesame oil was used the most (40.0%), followed by a mixture of olive oil and sesame oil (25.0%), and 21.7% used male frankincense. The majority (78.4%) sought medical advice for their post-infection cough, either from general pediatricians (39.5%) or via specialist pediatric pulmonology consultations (30.9%). A total of 11.0% with a residual cough reported having pets at home, while 27.2% reported secondhand smoke exposure in the household. Before infection with COVID-19, only 32.6% were diagnosed with asthma, while 68.2% reported a diagnosis of atopic skin. Conclusions: There was a high prevalence of residual cough post-COVID-19, extended for a minimum of two months, and the characteristics of the cough were very similar to those of asthmatic patients. There was still a high prevalence of using cough syrup and herbal remedies, especially olive oil, sesame oil, and male frankincense. A residual cough adversely affected school attendance in daily activities, and there was a high prevalence of other siblings in the family being affected. The study showed that a minority of patients were seen by the pulmonologist; luckily, long COVID was rare in our study, and so further studies are highly needed to confirm the association with asthma. More educational programs are highly needed regarding herbal remedies and cough syrup.